2017
DOI: 10.5465/amj.2013.1082
|View full text |Cite
|
Sign up to set email alerts
|

Why and When Leaders’ Affective States Influence Employee Upward Voice

Abstract: for their helpful comments on earlier drafts of this paper. We also thank Brent Scott and three anonymous reviewers for their helpful guidance and suggestions in the review process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
212
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 192 publications
(232 citation statements)
references
References 123 publications
(181 reference statements)
9
212
2
Order By: Relevance
“…This highlights how public expressions of voice by in-group members may not be perceived by managers as strong violations of loyalty and mutual support expectations, but instead might be perceived as less threating to their social status. In line with our findings, prior research has indicated that employees having high quality relationships with their managers have a stronger sense of psychological safety and, as a result, are less concerned that their voice might be perceived as a threat by managers (Liu et al, 2017). We complement such studies by highlighting that high LMX with the voicing employee colours managerial evaluation of possible image threats associated with voice in public settings.…”
Section: Theoretical Contributionssupporting
confidence: 88%
See 3 more Smart Citations
“…This highlights how public expressions of voice by in-group members may not be perceived by managers as strong violations of loyalty and mutual support expectations, but instead might be perceived as less threating to their social status. In line with our findings, prior research has indicated that employees having high quality relationships with their managers have a stronger sense of psychological safety and, as a result, are less concerned that their voice might be perceived as a threat by managers (Liu et al, 2017). We complement such studies by highlighting that high LMX with the voicing employee colours managerial evaluation of possible image threats associated with voice in public settings.…”
Section: Theoretical Contributionssupporting
confidence: 88%
“…Furthermore, given increased complexity in today's organizations, employees' input might be critical for identifying emerging issues and problems (Edmondson, 2003). Not surprisingly, extensive research indicates that voice improves managers' decision-making (Morrison & Milliken, 2000), helps to avoid errors (Edmondson, 2003), and enhances innovation (Liu, Song, Li, & Liao, 2017). The importance of voice for effective organizational functioning stimulated research into factors that promote employees to express their ideas, opinions, or concerns (see Morrison, 2011Morrison, , 2014.…”
Section: General Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…At the team level, we investigate and verify the mechanism of inclusive leadership on team performance on the basis of social exchange theory. Prior research has examined many factors that affect employee voice behavior, such as psychological antecedents (Liang et al, 2012), HR practice (Conway et al, 2016), leaders' positive affect (Liu et al, 2017), etc. While few studies investigated the relationship between inclusive leadership and employee voice behavior.…”
Section: Discussionmentioning
confidence: 99%